THE VALUES OF ISLAMIC EDUCATION IN THE STORY OF IBRAHIM P.B.U.H (Analysis Of Chapter Al-An'am Verses 74-81 And Chapter Al-Anbiyâ 51-70). - Rahman Sutomo, Syamsu Nahar , Abdullah AS (Pascasarjana UIN Sumatera Utara, 2019)
Abstrak: The purpose of this study is to examine the content of Islamic education values in the story of Prophet Ibrahim As in chapter Al-an'am verses 74 to 81 and chapter Al-Anbiyâ verses 51 to 70. Both stories have a thematic relationship from the message they carry. If at chapter Al-an'am verses 74-81, Prophet Ibrahim p.b.u.h found the presence of God by observing the signs in nature then in chapter Al-Anbiyâ verse 51-70, the prophet Ibrahim p.b.u.h conveyed instructions about the presence of God to his people by means of discussion to his people. The methodology used in the study is the Library Study Method. This research belongs to the literature study using the method of content analysis with the Tahlili Method. There is also the research method used is the method of interpretation of the maudhu'i, namely the method of interpreting the Qur'an thematically by summarizing the verses of the Koran that are relevant to the values of education to be studied. The data sources used in this study are the Qur'anic translation of the Ministry of Religion of the Republic of Indonesia, the exegesis of Ibn Kathir, the exegesis of Muhammad Quraiys Shihab al-Misbah, the exegesis of Muhammad Mutawalli Sya'rawi and the exegesis of Fi Zilal Quran sayyid qhutub. The results of this study show the values of Islamic education in the aspects of Aqidah, the story of Prophet Ibrahim p.b.u.h in the chapter Al-an'am verses 74-81 teaches the values of true Aqeedah as follows: 1. The value of Aqeedah. Almighty Allah will not have the